Improvement on Waste Segregation Knowledge by Verbal and Visual Prompt in Indonesia International Institute for Life Sciences (i3L) - Shirleen, Deborah; Kho, Katherine (Indonesia International Institute for Life Sciences, 2023)
In the face of the detrimental effect from the abundant waste, humans were left with no choice but to cycle them. Waste sorting, an important step to maximize the recyclables resources, is essential to be performed. To reinforce the waste sorting behavior, this study observed the impact of verbal prompt intervention. The experiment was done at a higher education institution, Indonesia International Institute for Life Sciences (i3L), that integrates sustainability education into their curriculum. This study observed convenient sampling of one group, pre- and post- intervention. Volunteers stand by and notify wrong waste generators for one hour in the communal cafeteria for one month, after one week of baseline observation. The observation revealed a sufficient number of knowledge on waste sorting on the pre-intervention baseline (75%). The presence of the prolonged intervention increased the number of correct waste sorting to 89.68% in the fourth week of intervention. Nonetheless, a survey conducted to confirm the cause of change, disclosed that the community’s heightened proper waste behavior is independent of the direct reminder, but rather due to the presence of the notifying volunteer. Therefore the root of waste segregation behavior improvement was more than just from verbal reminder, but from the presence of the rangers that enforces the rules.